Listeria monocytogenes in Almond Meal: Desiccation Stability and Isothermal Inactivation - Zhu, Meijun; Song, Xia; Shen, Xiaoye; Tang, Juming (Frontiers in Microbiology, 2020)
Almond is one of the most consumed tree nuts and also a common ingredient used in a variety of food products. Recent almond butter recalls due to potential contamination of Listeria monocytogenes highlight the need to control L. monocytogenes in almond products. The objectives of this study were to examine the stability of L. monocytogenes in almond meal during extended storage and further analyze thermal resistance of L. monocytogenes in almond meal of controlled moisture contents or water activity (aw) using thermal death treatement (TDT) cells and thermal water activity (TWA) cells, respectively. L. monocytogenes maintained a stable population in almond meal for 1 year at 4C regardless of aw; however, we observed about 1.69 and 2.14 Log10 CFU/g reduction of L. monocytogenes in aw 0.25 and 0.45 almond meal over 44-48 weeks of storage at 22C. Under all test conditions using either TDT or TWA cells, the inactivation kinetics of L. monocytogenes in almond meal fitted the log-linear model well; thermal resistance of L. monocytogenes in almond meal was inversely related to aw of samples. D75-/D80- values of L. monocytogenes in aw 0.25 and 0.45 almond meal obtained using TDT cells were 47.6/22.0 min versus 17.2/11.0 min, respectively. D80-, D85- and D90- values of L. monocytogenes in aw 0.25 almond meal obtained using TWA were 59.5 ± 2.1, 27.7 ± 0.7 and 13.2 ± 1.1 min, respectively, in contrast to 22.0 ± 1.1, 10.6 ± 0.2 and 4.6 ± 0.4 min obtained using TDT cells. The z-value of L. monocytogenes in aw 0.25 almond meal was not affected by TWA and TDT cell type (15.4-15.5°C), while z-value of L. monocytogenes in aw 0.45 almond meal was 10C higher than that in aw 0.25 almond meal. This study contributes to our understanding of L. monocytogenes in nuts and impacts of aw on the development of thermal resistance in low-moisture foods.